2009
DOI: 10.1103/physrevb.80.125308
|View full text |Cite
|
Sign up to set email alerts
|

Strong to weak localization transition and two-parameter scaling in a two-dimensional quantum dot array

Abstract: The transition from strong to weak localization behavior was observed in two-dimensional Ge/Si quantum dot structure under the variation in the quantum dot occupancy, their areal density and annealing of the structures at 480-625°C. To clarify the carrier transport mechanism and separate the hopping and diffusive regimes, the temperature dependence of conductance and conductance nonlinearity were analyzed in the structures with different correlations between the disorder and interaction. It was shown that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
2
16
0
2
Order By: Relevance
“…Results and discussions 3.1. Temperature dependence of conductance Fig 1a. demonstrates the temperature dependence of sheet conductance as Arrhenius plots for the following samples: for SD samples with filling factor ν ≈2.4 annealed at different temperatures (number 2-6), for SD sample with ν ≈2 annealed at 550 • C (7) and for the sample with double density of dots (ν ≈3) in zero magnetic field (1). One can see that the conductance strongly depends on sample parameters and changes by the several order of magnitude.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Results and discussions 3.1. Temperature dependence of conductance Fig 1a. demonstrates the temperature dependence of sheet conductance as Arrhenius plots for the following samples: for SD samples with filling factor ν ≈2.4 annealed at different temperatures (number 2-6), for SD sample with ν ≈2 annealed at 550 • C (7) and for the sample with double density of dots (ν ≈3) in zero magnetic field (1). One can see that the conductance strongly depends on sample parameters and changes by the several order of magnitude.…”
Section: Methodsmentioning
confidence: 96%
“…Our previous study of temperature dependence of conductance and its non-linearity in 2D Ge/Si quantum dot (QD) array [1] showed that change of the structural parameters of the system results in the transition from strong (SL) to weak localization (WL) behavior and, respectively, from hopping to diffusive transport. Different transport regimes should be characterized by different behavior of magnetoresistance (MR).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the low temperature parts (<10 K) shows that the temperature dependencies of conductance for both samples are described by ES law confirmed the strong carriers localization in the structure under study. The small temperature of the transition from the band to hopping transport, as compared to Ge/Si QDs structures [30], is explained by smaller ionization energy of Sb in Ge than in Si.…”
Section: Electron Localization: Transport Propertiesmentioning
confidence: 94%
“…• C temperatures resulted in a considerable increase of the conductance up to the observation of transition from hopping to the diffusion regime [30]. This was explained by smoothing of the localization potential and the corresponding increase of the wave functions overlapping due to a smearing of the QDs caused by Ge-Si intermixing.…”
Section: Electron Localization: Transport Propertiesmentioning
confidence: 98%
See 1 more Smart Citation